MOTOR NERVE CONDUCTION and REPETITIVE NERVE STIMULATION IN CAPTIVE RING-TAILED COATI (NASUA NASUA) - Mortari, Ana Carolina [UNESP]; Rahal, Sheila Canevese [UNESP]; Resende, Antonio de Lima [UNESP]; Teixeira, Carlos Roberto [UNESP]; Friciello Teixeira, Rodrigo Hidalgo; Mendes, Guilherme Maia [UNESP] (Amer Assoc Zoo Veterinarians, 2012)
There are few electrophysiologic studies in wild animals. The aim of this study was to determine normal data for motor nerve conduction studies and repetitive stimulation in sciatic-tibial and ulnar nerves in clinically normal captive coati. Eight adult ring-tailed coatis (Nasua nasua), two females and six males weighing 68 kg, were used. Average nerve conduction velocity was 70.81 m/sec (standard deviation [SD] = 3.98) and 56.93 m/sec (SD = 4.31) for the sciatic-tibial and ulnar nerves, respectively. Repetitive stimulation responses demonstrated minimal variations of the area of the compound muscle action potentials at low (3 Hz) and high (20 Hz) frequencies. The maximal obtained decremental area response was 8%. These normal data of conduction studies may be used in assessing abnormalities for clinical diagnosis. In addition, the obtained normal repetitive stimulation data were similar to dogs and humans and may be used for post- and presynaptic disturbances of the neuromuscular transmission in coatis.
Keywords: Coati; motor nerve conduction velocity; neurotransmission; electrophysiologic study; repetitive nerve stimulation